2009
DOI: 10.1093/hmg/ddp373
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting regulates mammalian snoRNA-encoding chromatin decondensation and neuronal nucleolar size

Abstract: Imprinting, non-coding RNA and chromatin organization are modes of epigenetic regulation that modulate gene expression and are necessary for mammalian neurodevelopment. The only two known mammalian clusters of genes encoding small nucleolar RNAs (snoRNAs), SNRPN through UBE3A(15q11–q13/7qC) and GTL2(14q32.2/12qF1), are neuronally expressed, localized to imprinted loci and involved in at least five neurodevelopmental disorders. Deficiency of the paternal 15q11–q13 snoRNA HBII-85 locus is necessary to cause the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 56 publications
7
70
0
Order By: Relevance
“…We noticed with interest that beaded structures were visualized at two different non-repeated human, ~400 kb regions (MHCII and 22q) in their natural chromatin context (Muller et al, 2004), again strengthening the notion that beaded DNA FISH signals are common features of decondensed chromatin rather than simply due to the repeated structure or the imprinted status of snoRD genes. While this manuscript was under revision, LaSalle's group independently reported outstanding, neuronal allele-specific decondensation (highly reminiscent of our results) at the same two loci investigated by us (Leung et al, 2009). With 200 kb as an upper limit, we estimate a packing ratio at the snoRNA gene loci ranging from ~1/70 to ~1/30 for bead-like DNA FISH signals with for three and 6-7 pinpoint DNA signals, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…We noticed with interest that beaded structures were visualized at two different non-repeated human, ~400 kb regions (MHCII and 22q) in their natural chromatin context (Muller et al, 2004), again strengthening the notion that beaded DNA FISH signals are common features of decondensed chromatin rather than simply due to the repeated structure or the imprinted status of snoRD genes. While this manuscript was under revision, LaSalle's group independently reported outstanding, neuronal allele-specific decondensation (highly reminiscent of our results) at the same two loci investigated by us (Leung et al, 2009). With 200 kb as an upper limit, we estimate a packing ratio at the snoRNA gene loci ranging from ~1/70 to ~1/30 for bead-like DNA FISH signals with for three and 6-7 pinpoint DNA signals, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…1D, bottom) that presumably reflect specific higher-order chromatin organization at highly expressed, tandemly repeated arrays of non-coding DNA in decondensed chromatin. Indeed, they recall DNA FISH patterns recently documented at three other imprinted repeated small RNA gene clusters that, notably, also give rise to huge amounts of nuclear-retained repeated non-coding RNA species (Leung et al, 2009;Vitali et al, 2010). Whether high expression of imprinted non-coding RNA genes plays a role in chromatin structure is an appealing hypothesis that needs to be tested experimentally.…”
Section: Resultsmentioning
confidence: 79%
“…We previously demonstrated that the paternal Snrpn-Ube3a chromatin becomes decondensed in a transcription-dependent and DNase-sensitive manner in postnatal neurons (28). Because topotecan reduces transcription of Ube3a-ATS, we investigated its effect on the chromatin structure of the maternal and paternal alleles by performing DNA FISH for the Snrpn-Ube3a locus on WT and Snord116del neurons.…”
Section: Resultsmentioning
confidence: 99%